ANALISIS KOMPARATIF DAN SINTESA TEORI BELAJAR KONVENSIONAL DENGAN TEORI BELAJAR DALAM ISLAM - Muhammad Husni (PEDAGOGIK : JURNAL PENDIDIKAN, 2018)
Learning is a necessity and plays an important role in human life. This is because humans are born as a weak creature who can not do anything and know nothing, he is only equipped with physical and spiritual potential. So it is reasonable to see why and how humans are affected by how they learn. Therefore learning is the "key term" that is most vital in the business of education. So without learning actually there is no education. Given how urgent learning, the term the theory of learning, which is the collection of general principles that are related to an explanation of a number of facts and discoveries related to learning events. Theory of learning during this time mostly from the west who have a different orientation with Islam. Sadly Muslims adopt such theories uncritically.